The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/hep.32581
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid p38 activation maintains macrophage–liver crosstalk and BAT thermogenesis through IL‐12–FGF21 axis

Abstract: Obesity features excessive fat accumulation in several body tissues and induces a state of chronic low-grade inflammation that contributes to the development of diabetes, steatosis, and insulin resistance. Recent research has shown that this chronic inflammation is crucially dependent on p38 pathway activity in macrophages, suggesting p38 inhibition as a possible treatment for obesity comorbidities. Nevertheless, we report here that lack of p38 activation in myeloid cells worsens high-fat diet-induced obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our group has shown that the immune system regulates body weight by influencing AT thermogenesis (Crespo et al, 2023 ), and we observed higher BAT temperature in mice lacking p38 activation in T cells. To confirm these differences under thermoneutral conditions, we placed CD4-Cre and MKK3/6 CD4-KO mice at 30 °C throughout the entire HFD feeding.…”
Section: Resultssupporting
confidence: 58%
“…Our group has shown that the immune system regulates body weight by influencing AT thermogenesis (Crespo et al, 2023 ), and we observed higher BAT temperature in mice lacking p38 activation in T cells. To confirm these differences under thermoneutral conditions, we placed CD4-Cre and MKK3/6 CD4-KO mice at 30 °C throughout the entire HFD feeding.…”
Section: Resultssupporting
confidence: 58%
“…Our findings further demonstrate that Smad2/3 or p38 inhibitors can mimic the effects induced by MSTN knockdown in brown adipocytes. Additionally, previous studies have indicated that the p38 signaling pathway can regulate the expression of Klf4 and Fgf21 (41,52). We herein addressed a pathway for Myostatin intracellular signals.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative explanations may include stimulation of insulin-independent glucose uptake mechanisms and/or altered utilization of energy sources. MAP3K ASK1 is a major ROS-induced activator of p38 and JNK in cell lines and mouse models (44) and has also been linked to metabolic regulation (68)(69)(70). Other ROS-activated MAP3Ks that have been implicated in metabolic control are MLK2/3 and MAP3K4 (71,72).…”
Section: Discussionmentioning
confidence: 99%